In vivo embryo production in Lacaune ewes collected by transcervical technique - Figueira, Lucas Machado (2019)
Multiple ovulation and embryo transfer (MOET) programs has the potential to accelerate the genetic improvement of sheep breeds of productive interest such as Lacaune. The general objective of this thesis was to evaluated strategic points to increase the efficiency of MOTE applying the non-surgical embryo recovery (NSER) technique following cervical dilation treatment in Lacaune ewes. In the first study, the zootechnical interest of the breed was reviewed. In the second, the ultrasonographic cervical evaluation was incorporated in the routine of procedures aiming NSER, to evaluate its potential to predict the transcervical penetration by cervical misalignment. Two different times was chosen to perform the exam: (1) 12 h after estrus onset in the first study and (2) immediately before NSER in the third study. The evaluating at the estrus was inefficient due to the high incidence of false negatives (52%). However, the evaluation before NSER, the sensibility and specificity were 100%, demonstrating the potential of the tool to donors selecting. The third study evaluated the effects of the duration of progestogen-based estrus induction protocols for six (G-6) or nine (G-9) days on preovulatory follicular dynamic, ovulatory response and embryo yields in Lacaune ewes by NSER technique. A rate of 95.2% of transcervical penetration was achieved 5 to 6 days after ovulation. There was higher (P < 0.05) ovulatory response (2.9 ± 0.3 vs 1.9 ± 0.3) and embryo yield (1.3 ± 0.4 vs 0.4 ± 0.2) in G-9 compared to the G-6. In the fourth study, the ewes were submitted again to 6 and 9-days protocols, but superovulated with the 133 mg of porcine FSH (pFSH). The G-9 outperformed G-6 days protocol, showing higher (P < 0.05) embryo yield after NSER (3.5 ± 1.1 vs 1.8 ± 0.7) performed on day 6 to 7 after estrus onset. As the pFSH dose used was inadequate to increase superovulatory (SOV) and embryo yield responses, it was conducted a fifth study, using the G-9 protocol and comparing the doses of 100 (G-100) and 200 mg (G-200) of pFSH. The 100 mg dose was insufficient to recruitment follicular and there were higher (P < 0.05) SOV response in G-200 (11.6 ±1.2) than in G-100 (2.6 ± 0.7). The structures recovery rate and the number of viable embryos were higher in G-200 (67.8% and 6.9 ± 1.1) than in G-100 (27.6% and 1.0 ± 0.5). In the sixth study, the recovered embryos were cryopreserved by either slow freezing (SF) and vitrification techniques and were randomly used for fixed-time embryo transfer (FTET) to synchronized recipients. Although challenged to cellular damage inherent in the cryopreservation process, embryos recovered by NSER after cervical dilation treatment were able to establish pregnancy and lambing after FTET, but satisfactory results were obtained only with the SF technique (39.4 and 20.9 %, respectively). The present thesis presents results that attest the feasibility of carrying out multiple ovulation and embryo transfer programs based on NSER in Lacaune ewes.